Effectiveness of ozone therapy compared to other therapies for low back pain: a systematic review with meta-analysis of randomized clinical trials - de Andrade,Raul Ribeiro (2019)
Abstract Background and objectives: Low back pain is a prevalent disease in the adult population, whose quality of life is considerably affected. In order to solve this problem, several therapies have been developed, of which ozone therapy is an example. Our objective in this study was to determine the effectiveness of ozone therapy for lumbar pain relief in adult patients compared to other therapies (steroid and placebo). Method: We used randomized clinical trials to compare the effectiveness of ozone and other therapies for lumbar pain relief in adults (Prospero: CRD42018090807). Two independent reviewers searched the Medline (1966–April/2018), Scopus (2011–May/2018), Lilacs (1982–May/2018), and EMBASE (1974–March/2018) databases. We use the terms ozone and pain as descriptors. The primary variable was pain relief and the secondary ones were complication, degree of satisfaction, quality of life and recurrence of pain. Results: Of the 779 identified articles, six selected clinical trials show that ozone therapy is more effective for lumbar pain relief; however, they were mostly classified as having a high or uncertain risk of bias (Cochrane Handbook). The meta-analysis regarding the effectiveness of pain relief did not show a significant difference between groups in the three-month period (RR = 1.98, 95% CI: 0.46–8.42, p= 0.36; 366 participants). It also showed greater effectiveness of the ozone therapy at six months compared to other therapies (steroid and placebo) (RR = 2.2, 95% CI: 1.87–2.60, p< 0.00001; 717 participants). Conclusions: The systematic review has shown that ozone therapy used for six months for lumbar pain relief is more effective than other therapies; however, this result is not definitive as data from studies with moderate to high risk of bias were used.